Effectiveness of a nursing intervention in decreasing the anxiety levels of family members of patients undergoing cardiac surgery: a randomized clinical trial - Letícia Hamester; Emiliane Nogueira de Souza; Cibele Cielo; Maria Antonieta Moraes; Lúcia Campos Pellanda
ABSTRACT Objective: to verify the effectiveness of nursing orientation provided to families of patients in the immediate post-operative following cardiac surgery before the first visit to the post-anesthesia care unit, in decreasing anxiety levels, compared to the unit's routine orientation. Method: open randomized clinical trial addressing family members in the waiting room before the first visit in the immediate post-operative period. The family members assigned to the intervention group received audiovisual orientation concerning the patients' conditions at the time and the control group received the unit's routine orientation. Outcome anxiety was assessed using the STAI-State. Results: 210 individuals were included, 105 in each group, aged 46.4 years old on average (±14.5); 69% were female and 41% were the patients' children. The mean score obtained on the anxiety assessment in the intervention group was 41.3±8.6, while the control group scored 50.6±9.4 (p<0.001). Conclusion: a nursing intervention focused on providing guidance to families before their first visit to patients in the immediate post-operative period of cardiac surgery helps to decrease the levels of anxiety of companions, making them feel better prepared for the moment. ReBEC (Brazilian Clinical Trials Registry) and The Universal Trial Number (UTN), No. U1111-1145-6172.